Ginsenoside Rb1, a principal effective ingredient of Panax notoginseng, produces pain antihypersensitivity by spinal microglial dynorphin A expression. (March 2023) - Shoaib, Rana Muhammad; Ahsan, Muhammad Zaeem; Akhtar, Usman; Ahmad, Khalil Ali; Ali, Usman; Deng, Men-Yan; Li, Xin-Yan; Wang, Yong-Xiang
Abstract: Panax notoginseng (Chinese ginseng, Sanqi), one of the major ginseng species, has been traditionally used to alleviate different types of chronic pain. The raw P. notoginseng powder is commonly available in China as a non-prescription drug to treat various aliments including arthritic pain. However, strong scientific evidence is needed to illustrate its pain antihypersensitive effects, effective ingredients and mechanism of action. The oral P. notoginseng powder dose-dependently alleviated formalin-induced tonic hyperalgesia, and its total ginsenosides remarkably inhibited neuropathic pain hypersensitivity. Ginsenoside Rb1, the most abundant ginsenoside of P. notoginseng, dose-dependently produced neuropathic pain antihypersensitivity. Conversely, ginsenosides Rg1, Re and notoginseng R1, the other major saponins from P. notoginseng, failed to inhibit formalin-induced tonic pain or mechanical allodynia in neuropathic pain. Ginsenoside Rb1 metabolites ginsenosides Rg3, Compound-K and protopanaxadiol also had similar antineuropathic pain efficacy to ginsenoside Rb1. Additionally, intrathecal ginsenoside Rb1 specifically stimulated dynorphin A expression which was colocalized with microglia but not neurons or astrocytes in the spinal dorsal horn and primary cultured cells. Pretreatment with microglial metabolic inhibitor minocycline, dynorphin A antiserum and specific κ-opioid receptor antagonist GNTI completely blocked Rb1-induced mechanical antiallodynia in neuropathic pain. Furthermore, the specific glucocorticoid receptor (GR) antagonist Dex-21-mesylate (but not GPR30 estrogen receptor antagonist G15) also entirely attenuated ginsenoside Rb1-related antineuropathic pain effects. All these results, for the first time, show that P. notoginseng alleviates neuropathic pain and ginsenoside Rb1 is its principal effective ingredient. Furthermore, ginsenoside Rb1 inhibits neuropathic pain by stimulation of spinal microglial dynorphin A expression following GR activation. Graphical Abstract: ga1 Highlights: Novel therapies are required to treat neuropathic pain due to limited efficacy of available treatments. Panax notoginseng powder and its total ginsenosides remarkably inhibit pain hypersensitive states. Ginsenoside Rb1 is the principal saponin in Panax notoginseng to ameliorate neuropathic pain. Ginsenoside Rb1 stimulates spinal microglial dynorphin A expression to alleviate neuropathic pain probably by membrane glucocorticoid receptor activation.